HUBUNGAN ANTARA SIFAT KIMIA TANAH DENGAN SERAPAN HARA TANAMAN TEH DI PTPN VI JAMBI - Arini Ayu Ardianti; Faris Nur Fauzi Athallah; Restu Wulansari; Kurniawan Sigit Wicaksono (Jurnal Tanah dan Sumberdaya Lahan, 2022)
Healthy soil could support plant growth by optimizing the availability of nutrients. The availability of nutrients influences the health of tea plants. Nutrient deficiencies would affect the plant physiology that exhibits the plant withering. This study aimed to define the relationship between soil nutrient availability with plant nutrient uptake. This research was conducted by managing secondary data soil chemical properties, and tea plant nutrients analyzed statistically with Pearson correlation. This study only found a significant correlation between soil pH with P and Mg uptake. Correlation results between soil nutrient and plant nutrient uptake obtained a significantly negative correlation on soil pH with P and Mg nutrients with a correlation value of pH-P (r=-0.52), pH-Mg (r=-0.52). There was no correlation between other soil nutrients and plant nutrient uptake. The results of this study can be usedÂ Â  to determine the dose of fertilization and the management recommendation of tea plants.